2004
DOI: 10.1021/jf035218u
|View full text |Cite
|
Sign up to set email alerts
|

The Composition of Grain and Forage from Glyphosate Tolerant Wheat MON 71800 Is Equivalent to That of Conventional Wheat (Triticum aestivum L.)

Abstract: Glyphosate tolerant wheat MON 71800, simply referred to as MON 71800, contains a 5-enolpyruvylshikimate-3-phosphate synthase (EPSPS) protein from Agrobacterium sp. strain CP4 (CP4 EPSPS) that has a reduced affinity for glyphosate as compared to the endogenous plant EPSPS enzyme. The purpose of this work was to evaluate the compositional equivalence of MON 71800 to its nontransgenic parent as well as to conventional wheat varieties. The compositional assessment evaluated the levels of proximates, amino acids, f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(39 citation statements)
references
References 23 publications
2
37
0
Order By: Relevance
“…The published studies observed similar results in different GM plants, like potato metabolome (Catchpole et al 2005) and proteome (Lehesranta et al 2005), tomato (Corpillo et al 2004), or transcriptome and metabolome of GM wheat (Baker et al 2006;Baudo et al 2006). Complex analyses of glyphosate tolerant wheat MON 71800 found no significant changes in 88 different components compared with wt plants (Obert et al 2004). Comparative analyses of different GM plants regarding substantial equivalence have been reviewed by Cellini et al (2004).…”
Section: Comparison Of Different Wheat Linesmentioning
confidence: 88%
“…The published studies observed similar results in different GM plants, like potato metabolome (Catchpole et al 2005) and proteome (Lehesranta et al 2005), tomato (Corpillo et al 2004), or transcriptome and metabolome of GM wheat (Baker et al 2006;Baudo et al 2006). Complex analyses of glyphosate tolerant wheat MON 71800 found no significant changes in 88 different components compared with wt plants (Obert et al 2004). Comparative analyses of different GM plants regarding substantial equivalence have been reviewed by Cellini et al (2004).…”
Section: Comparison Of Different Wheat Linesmentioning
confidence: 88%
“…These studies include assessments of soy (Padgette et al 1996;Taylor et al 1999), corn (Ridley et al 2002;Sidhu et al 2000;Herman et al 2004), cotton (Bertrand et al 2005;Nida et al 1996), rice (Oberdoerfer et al 2005), wheat (Obert et al 2004), andalfalfa (McCann et al 2006). As mentioned earlier, reports of omics studies on biotechnology-derived plants indicate that these are typically more closely related to the isogenic parental strain used in their development than the parental strain is to other members of the same species (see earlier references).…”
Section: Compositional Comparisonsmentioning
confidence: 99%
“…Conversely, the same lines showed elevation in proline and ␄ -aminobutyric acid (GABA) at the alternative environment. Obert et al (2004) also failed to find any significant differences between grain field plots of herbicide-resistant and control lines using a combined GC and LC approach.…”
Section: Grain Crops 731 the Cerealsmentioning
confidence: 94%